“Você deveria ter vergonha de viver num país com tantos analfabetos”: a campanha publicitária do Mobral na Revista Veja (1970-1975) - Silva, Danielly Cardoso da (2019)
This Project is in the field of the History of Education and is linked to a line of research State, Policies and History of Education of the Program of Postgraduate studies in Education of the College of Education of the Federal University of Goiás. It is a historical research, that uses theoretical-methodological contributions of cultural history, that proposes a amplification in the uses of the sources and their political, contextual and cultural characteristics as elements of their own time. Among others, it’s supported in authors like Burke (1994, 2011), Chartier (1988), Pesavento (2005). In the line of the History of Education, the research circumscribe itself in the thematic of the Education of Youth and Adults and has as an objective comprehend the historical context of the implantation of Mobral and its characteristics; situate the products that composed the advertising campaign of Mobral in the digital archive of the Revista Veja; analyze this advertising campaign, looking to comprehend the directions, concepts and elements used in the representation of the project; connect the representation of Mobral as an educational project of the military dictatorship. The sources used were, almost in its entirety, in digital format, what contributed to the access in agile conditions and preservation of the originals. It explored copies of the Revista Veja, where it was located advertisement and reports that were part of the advertising campaign analyzed. There was confrontation of the images, representations, characters and elements particular of the context of the dictatorship of whom the campaign integrates, such as the authority imposition of adhesion from the population to the project, divulgation of the redemptive and grandiose proposition, opposition between illiberalism and development, the cult to the homeland, national value and maintenance of the strategic relations with the business communities of communication and other subjects listed. Such an analyzation enabled the comprehension that Mobral was an educational proposition destinated to the education of adults, with particular characteristics of its time. The representations presented in the advertising campaign could have contributed to the propagation of a memory allied to the callings made during the military dictatorship, due to the intense movement of propaganda linked to distant press agencies. Even if Mobral doesn’t exist as an education practice in the present, I seems to maintain itself associated to the new educational projects of youth and adults for distant generations.